THE EFFECT OF NON-PERFORMING LOANS, RETURN ON ASSETS, RETURN ON EQUITY, AND INTEREST RATES ON STOCK PRICES (EMPIRICAL STUDY OF FINANCING SERVICES SUB-SECTOR COMPANIES ON THE INDONESIA STOCK EXCHANGE FOR THE 2019-2023 PERIOD) - Samuel Ferdinand Yesianda; Astrid Dita Meirina Hakim (Antis Publisher, 2025)
Objective: This study aims to determine the effect of non-performing loans, return on assets, return on equity and interest rates on stock prices in financing service sub-sector companies on the Indonesia Stock Exchange for the 2019-2023 period. Method: The sample of this study were 12 companies in the financing services sub-sector listed on the Indonesia Stock Exchange for the 2019-2023 period. This study uses a panel data regression statistical analysis tool assisted by the Eviews version 13 program and Microsoft Excel 2019. Results: The results of this study indicate that non-performing loans (NPL) and return on assets (ROA) have no effect on stock prices. Interest rates have a negative and significant effect on stock prices. On the other hand, return on equity (ROE) has a positive and significant effect on stock prices. Novelty: There is no explicit statement of novelty in the abstract. However, it can be inferred that the novelty lies in analyzing the simultaneous impact of NPL, ROA, ROE, and interest rates on stock prices specifically in the financing service sub-sector on the Indonesia Stock Exchange over the 2019–2023 period, using panel data regression with Eviews 13.